The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/jvi.02276-16
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudorabies Virus Glycoprotein gE/gI Complex Suppresses Type I Interferon Production by Plasmacytoid Dendritic Cells

Abstract: Plasmacytoid dendritic cells (pDC) play a central role in the antiviral immune response, both in the innate response and in shaping the adaptive response, mainly because of their ability to produce massive amounts of type I interferon (TI-IFN). Here, we report that cells infected with the live attenuated Bartha vaccine strain of porcine alphaherpesvirus pseudorabies virus (PRV) trigger a dramatically increased TI-IFN response by porcine primary pDC compared to cells infected with wild-type PRV strains (Becker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 64 publications
(87 reference statements)
5
40
0
Order By: Relevance
“…As a result, more virus particles may invade axon terminals of the DRG neurons and replicate in the cell bodies. A recent study showed that PRV-Becker inhibits the IFN response in swine plasmacytoid DCs, while PRV-Bartha elicits a much more robust type I IFN response in these cells (66). This difference was attributed to a deletion of the glycoprotein gE/gI gene complex in the genome of Bartha.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, more virus particles may invade axon terminals of the DRG neurons and replicate in the cell bodies. A recent study showed that PRV-Becker inhibits the IFN response in swine plasmacytoid DCs, while PRV-Bartha elicits a much more robust type I IFN response in these cells (66). This difference was attributed to a deletion of the glycoprotein gE/gI gene complex in the genome of Bartha.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lamote and colleagues demonstrated that PRV-Becker inhibits the IFN response in swine dendritic cells while PRV-Bartha induces a strong type I IFN response in these cells. This difference was attributed to the absence of the immunomodulatory glycoprotein gE/gI gene complex, in the genome of Bartha [137]. So far, the level of type I IFN has not been quantified in the swine URT and compared between PRV-Becker and PRV-Bartha infections.…”
Section: Why Prv-infected Swine Do Not Itchmentioning
confidence: 99%
“…For example, virulent PRV-Becker infection suppresses the expression of most IFNβ-stimulated genes in primary rat fibroblasts through inhibition of STAT1 tyrosine phosphorylation [23]. In addition, another study showed that PRV-Becker infection inhibits the IFN response in swine plasmacytoid dendritic cells (pDCs), while the attenuated vaccine strain PRV-Bartha elicits a much more robust type I IFN response in these cells [24]. This difference was attributed to a deletion of the glycoprotein gE/gI gene complex in the PRV Bartha genome.…”
Section: Introductionmentioning
confidence: 99%